Expansion of the North American amphipod Gammarus tigrinus Sexton, 1939 to the Neva Estuary (easternmost Baltic Sea) - Nadezhda A. Berezina (Oceanologia, 2007)
The North American gammaridean amphipod, Gammarus tigrinus, was found in the easternmost part of the Baltic Sea (Neva Estuary) near a new oil terminal. This species may well have been transportedto the Neva Estuary with ballast waters from the Finnish area of the Gulf of Finland, where it was recorded recently. In 2005, the mid-summer density of G. tigrinus was 27 indiv. m-2. By2006 this species had spread 100 km to the east from the first site, colonizing the northern coastal zone of the estuary. Its density reached 99-126 indiv. m-2. Fecund females and juvenilescontributed about 50% to the entire population density, which testifies to the successful reproduction and establishment of G. tigrinus in the Neva Estuary. There is a high risk of further expansions of G. tigrinus from the new area to the various lakes of Eastern Europe via inland canal-river systems, whichmay lead to unforeseeable changes in aquatic communities.